Analysis of the risk factors of delayed extubation after surgery for Ebstein’s anomaly - Yan He; Yu Feng; Ting-Zhou Zhang; Xing Fan; Yan Zhu; Hong-Sheng Zhang (Journal of Cardiothoracic Surgery)
Abstract Objective In this study, we aimed to screen the risk factors for delayed extubation after surgery for Ebstein’s anomaly (EA), determine the diagnostic cut-off values, and develop a prediction equation to accurately encourage rapid recovery after surgery. Methods The perioperative data of 76 pediatric patients undergoing EA surgery in the Surgical Department of the Pediatric Heart Center of Anzhen Hospital from September 2013 to September 2021 were retrospectively analyzed. Results Among these cases, 37 (48.6%) were male, with an average age of 4.67 (2, 11.19) years and an average weight of 18 (12.4, 37) kg. The median postoperative duration of mechanical ventilation was 18 (10, 24) h, and the duration of mechanical ventilation ≥ 24 h (75th percentile) was defined as delayed extubation. Body weight (11.25 kg) and preoperative oxygen saturation (SpO2) (95.5%) were protective factors, while the simplified Great Ormond Street Echocardiogram (GOSE) value (0.995) and the intraoperative cardiopulmonary bypass (CPB) time (135 min) were the risk factors. The prediction model was developed based on these indexes: logit (P) = 8.9 + (0.02 × CPB time) + (2.2 × simplified GOSE) – (0.14 × preoperative SpO2) − (0.06 × body weight), and the area under the receiver operator characteristic (ROC) curve was 83.4% (P < 0.01). Patients with delayed extubation had a longer intensive care unit stay and a higher incidence of adverse events (P < 0.01). Conclusion Low body weight, low preoperative SpO2, high GOSE value, and long intraoperative CPB time for pediatric patients with EA are likely to lead to prolonged postoperative duration of mechanical ventilation. For low-risk children, early extubation after surgery can be more actively encouraged; however, more care should be taken to avoid the risk of re-intubation.